Digital leadership role in developing business strategy suitable for digital transformation - Türk, Abdullah (Frontiers in Psychology, 2023)
Businesses must respond to the ecology in which they operate. Especially the rapid transformation of technology has increased the degree of dependency on the system. The main reason for this is perceived only as the technology costs brought by digital transformation. However, we understand from the bankruptcy of economically strong companies that this is not the real problem. This study looks at it from the perspective of leadership, which is an important skill for businesses. The research focuses on leadership roles needed to adapt to digital transformation. At this point, the roles of digital leadership and its contribution to businesses were investigated. At this point, we try to reveal the role of digital leadership with two different qualitative analyzes. In the research, semi-structured interviews were conducted with senior managers, phenomenological and content analysis was performed using Nvivo and MAXQDA qualitative analysis programs, and relevant confidential information was revealed. As a result of the research, it has been determined that there is an important link between time management and productivity while supporting system efficiency and transformation adaptation. In other words, a positive relationship has been determined between the success of digital transformation and digital leadership roles. In digital transformation, digital leadership has a role in the positive development of the relationship between the digital transformation process and business strategies. As a result, a perspective on how digital leadership can contribute to businesses that want to develop strategies suitable for the digital transformation process is presented.